O grêmio estudantil de uma escola municipal de ensino fundamental de São Paulo e a relação no processo de formação da cidadania dos alunos - Idelbrando, Amália Galvão (2012)
The present study aims at verifying the relationship between the actions of a Student´s Body of a Public Primary School on the Municipality of São Paulo city and the development process of establishing the students´ citizenship. This research has a qualitative approach. It included literature studies on the area and analysis of legal documents on the Student´s Body, aligned with an empirical research where meetings of Student´s Body and meetings of the School Board were observed by the researcher on their own school environment. The following people of the school were interviewed: the Principal, the President of the Student´s Body school´s group, the Professor in charge of the student´s collegiate and the teacher who helped on the Student´s Body implementation by means of flexible and semi-structured guidelines. The study was based on the theorists Apple and Beane (2001), Apple (1989,2006) and Gimeno Sacristán (1999,2001,2002), Gimeno Sacristán e Pérez Gómez (1998) among others. The results showed that the activity of the Student´s Body of a Public Primary School on the Municipality of São Paulo city is a space more tutored by teachers supervision rather than the political education upbringing on the way where these students development of a construction process of citizenship, criticism and autonomy in order to solve either collective or individual problems as well as for preparing them to intervene politically, enabling them to change their own reality. There are reminiscences of the arbitrary regime of the 1960s that had as goal the student´s political disarticulation, highlighting sports and recreation activities. The reflections of lack of politicization are felt, on the one hand, as the Student´s Body does not establish an organizational culture in their school, and on the other hand, for assuming specific characteristics of a class society. The school academic and administrative management, without including the Student´s Body as an established organization, expressed a tutoring and reproductive perspective without stimulating the expansion of political participation